The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.32983/2222-4459-2020-12-471-481
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Development of the Organization of Catering of Schoolchildren as an Integral Part of the Management of Modern Institutions of General Secondary Education

Abstract: The article is aimed at carrying out a comprehensive analysis and an evaluation of innovative processes that are currently taking place in the organization of school meals of general secondary education institutions (GSEI) of Ukraine and aimed at improving the management of their activities. To achieve the aim, general scientific and special research methods were used. The content essence of some concepts in the theory and practice of catering are closer defined. It is determined that innovations for the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…They are useful, and sometimes extremely necessary, even in the conditions of crisis phenomena and their consequences. This is confirmed by studies of the different scientists [8][9][10][11][12].…”
Section: Literature Reviewsupporting
confidence: 58%
See 2 more Smart Citations
“…They are useful, and sometimes extremely necessary, even in the conditions of crisis phenomena and their consequences. This is confirmed by studies of the different scientists [8][9][10][11][12].…”
Section: Literature Reviewsupporting
confidence: 58%
“…In our previous studies, the dichotomy of innovative transformations was identified [11]; the analysis of social innovations was carried out [18]; an assessment of the innovative potential of enterprises in various sectors of the economy during the deployment of the fourth wave of globalization was conducted [10]; the correlation between the new requirements for managers (in particular, HR-managers) of companies and the rapid development of digital innovative technologies that began to be actively used during the pandemic [19], etc.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation